Using interprofessional simulation to teach clinical interviewing for trauma. - Gallimore, Casey E.; Bryan, Gina M.; Fiegel-Newlon, Jennifer; Willits, Angela; Studer, Lynette; Jackson, Sherrelle P. (Journal of Interprofessional Care)
Approximately 83% of United States residents encounter trauma in their lifetimes, necessitating trauma-informed care education across all healthcare disciplines. Included in this is instruction and practice interviewing clients for trauma history. The University of Wisconsin–Madison's Nursing, Pharmacy, and Social Work faculties collaborated to create an interprofessional online simulation to enhance students' application of trauma-informed principles to clinical interviewing. The interprofessional format facilitated learning with, from, and about students across health profession programs. Development and refinement of the simulation were informed by program evaluation, incorporating feedback and outcomes from three iterations. Pre- and post-surveys using a combination of Likert-type scale and open-ended items were used to collect evaluation data. One hundred and seventy-seven students out of 223 (79% response rate) completed both surveys and were included in the analysis. Findings indicate that virtual, low-fidelity simulation – incorporating discussion, role-play, and debriefing – can advance students' understanding of trauma-informed principles and skills in interviewing for trauma, while also promoting interprofessional competencies. Students valued the opportunity to practice clinical interviewing for trauma in a low-stakes, safe environment, and to learn through peer observation. Future considerations involve exploring different delivery methods, reexamining optimal placement of the simulation within each program's curricula, and extending participation to other health disciplines.